Essential Role of Surface-Bound Complement Factor H in Controlling Immune Complex–Induced Arthritis - Banda, Nirmal K. (AAI, 2013)
Factor H (fH) is an endogenous negative regulator of the alternative pathway (AP) that binds polyanions as well as complement activation fragments C3b and C3d. The AP is both necessary and sufficient to develop collagen Ab–induced arthritis (CAIA) in mice; the mechanisms whereby normal control of the AP is overcome and injury develops are unknown. Although primarily a soluble circulating protein, fH can also bind to tissues in a manner dependent on the carboxyl-terminal domain containing short consensus repeats 19 and 20. We examined the role of fH in CAIA by blocking its binding to tissues through administration of a recombinant negative inhibitor containing short consensus repeats 19 and 20 (rfH19-20), which impairs fH function and amplifies surface AP activation in vitro. Administration of rfH19-20, but not control rfH3-5, significantly worsened clinical disease activity, histopathologic injury, and C3 deposition in the synovium and cartilage in wild-type and fH(+/−) mice. In vitro studies demonstrated that rfH19-20 increased complement activation on cartilage extracts and injured fibroblast-like synoviocytes, two major targets of complement deposition in the joint. We conclude that endogenous fH makes a significant contribution to inhibition of the AP in CAIA through binding to sites of immune complex formation and complement activation.